Pembelajaran Berbasis Alam dalam Membentuk Karakter Anak Usia Dini (Studi Analisis di TK Jogja Green School) - Mukaromah, Luluk (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This research is based on early childhood education, which is a golden period where thepotential opportunities and optimal development of children can be developed if facilitatedaccording to their needs. This is also to realize the Law of the Republic of Indonesia No. 20 of2003 concerning National Education System Article 1 that the readiness of young children toenter further education requires the development of efforts aimed at children from birth to the age of 6 carried out through the provision of educational stimuli in helping developmentphysical and psychological child. Therefore, early childhood education is developed creativelythrough the development of a Nature-based curriculum that has been carried out by JogjaGreen School. Nature-based curriculum is learning where the learning process is moreintegrated with nature. In this study the authors used qualitative research methods. Which in its implementation uses the method of observation and interviews. The results of research and discussion indicate the formation of children's character in time to time. From KB toKindergarten. Then it can be concluded that the Nature-based curriculum can stimulate everycharacter building of children both for family planning to kindergarten. Therefore, PAUDteachers and PAUD practitioners should understand the nature-based curriculum and be able to apply it.